Reduction of soluble CD163, substance P, programmed death 1 and inflammatory markers. (15th May 2015) - Tebas, Pablo; Spitsin, Sergei; Barrett, Jeffrey S.; Tuluc, Florin; Elci, Okan; Korelitz, James J.; Wagner, Wayne; Winters, Angela; Kim, Deborah; Catalano, Renae; Evans, Dwight L.; Douglas, Steven D.
<x xml:space="preserve">Abstract</x> Objective: We evaluated safety, antiviral, immunomodulatory and anti-inflammatory properties of aprepitant – a neurokinin 1 receptor antagonist. Design: Phase IB randomized, placebo-controlled, double-blinded study. Methods: Eighteen patients were randomized (nine to aprepitant and nine to placebo). The patients received once-daily treatment (375 mg aprepitant or placebo by oral administration) for 2 weeks and were followed off drug for 4 weeks. Results: There were no significant changes in the plasma viremia or CD4+ T cells during the dosing period. Aprepitant treatment was associated with significant decreases of median within patient change in percentages of CD4+ T cells expressing programmed death 1 (−4.8%; P = 0.04), plasma substance P (−34.0 pg/ml; P = 0.05) and soluble CD163 (−563 ng/ml; P = 0.02), with no significant changes in the placebo arm. Mean peak aprepitant plasma concentration on day 14 was 7.6 ± 3.1 μg/ml. The use of aprepitant was associated with moderate increases in total cholesterol, low-density lipoprotein and high-density lipoprotein (median change = +31 mg/dl, P = 0.01; +26 mg/dl, P = 0.02; +3 mg/dl, P = 0.02, respectively). Conclusion: Aprepitant was safe and well tolerated. At the dose used in this proof-of-concept phase IB study, aprepitant did not show a significant antiviral activity. Aprepitant-treated patients had decreased numbers of CD4+ programmed death 1-positive cells and decreased plasma levels of substance P and soluble CD163, suggesting that blockade of the neurokinin 1 receptor pathway has a role in modulating monocyte activation in HIV infection. Prospective studies in virologically-suppressed individuals are warranted to evaluate the immunomodulatory properties of aprepitant. Exposures exceeding those attained in this trial are more likely to elicit clinical benefit.